Optimizing Costs of Customer Attraction as a Competitiveness Factor - A. V. Katernyuk (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
In all spheres business experts try to raise competitiveness of the company by different ways, for instance at the expense of more efficient redistribution of available resources (costs). Objectives connected with modeling and optimizing resources used in advertising are becoming the most topical. Deeper knowledge in planning and conducting any marketing and advertising campaigns are in demand today among many specialists. The process of searching for and finding optimum costs of advertising in the Internet as a factor of the rise in the company sustainability can be successfully shaped through universal matrix methods of solution (e.g. simplex-method). Objectives which cannot be resolved by this method can be supplemented by such economic indicators, as profitability of investment and return on one ruble. The article summarizes the instrumental base dealing with estimating the efficiency of events connected with customer attraction to such a fast growing industry as internet-services. The author proposes besides traditional ways of expense optimization to take into account economic indicators connected with profitability of each sale channel. The following tools were used in the research: modeling, induction method, investment analysis, methods of statistics and formal logics, multi-criteria optimization, specific software meant for solving similar tasks, in particular special macros for excel table.